Penilaian Konsumen Terhadap Beberapa Atribut Dua Jenis Rokok Produk Sampoerna - Imam Hidayat, Syarif (Jurnal Riset Ekonomi dan Bisnis, 2008)
Up to now cigarette is always interesting consumer goods to many people in the world. Eventhough there is restriction by government in order not to smoke, really still do it as habit. In the other hand cigarette tax has a big contributed to national income so the issues always the hot topics discussion between pro and contra from time to time. The purpose of study is to analize some atributes of two cigarettes product like price, packaging, aroma, and taste affected consumer to buy it. With fishbein analysis shows that taste and aroma of cigarette A more likely by consumer than cigarette B’s attributes are packaging and taste more likely by consumer.Based on score cigarette A bigger than cigarette B  indicated that cigarette A more suitable and nearly customer expectation and customer satisfaction. So as recommended to make good strategy are cigarette A focused in middle up target and cigarette B toward to reach market in low until middle class consumer.Keywords : Consumer Behavior, Cigarette